ESTUDIOS SOBRE LA MICROBIOLOGIA DEL PULQUE IV COMPORTAMIENTO SEROLOGICO DE DOS DEXTRANAS DE LEUCONOSTOC - SANCHEZ MARROQUIN, AY; RODRIGUEZ, H (Instituto de Salubridad y Enfermedades Tropicales, CD MEXICO, DF, MEX, 1948)
3 Leuconostoc strains isolated from aguamiel and slightly different in their biochem properties from other known Leuconostoc strains, were used to obtain a highly viscous syrup from aguamiel with added sucrose to a concn of 25-70[degree] Brix and 1-4% o
AN ESC NAC CIENC BIOL
Keywords: ESTUDIOS, MICROBIOLOGIA, PULQUE, COMPORTAMIENTO SEROLOGICO, DOS DEXTRANAS, LEUCONOSTOC; CIENCIAS DE LA VIDA; MICROBIOLOGIA; PROCESOS MICROBIANOS